1999
DOI: 10.1037/h0087787
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of dropping out in time-limited, interpretive individual psychotherapy.

Abstract: Predictors of dropping out were focus on transference, significantly investigated for patients who participated differentiated dropouts from completers. in time-limited, interpretive individual psychotherapy in a randomized clinical trial. A sample of 22 dropouts was compared with a sample of 22 matched completers on both pretherapy and therapy process variables. None of the pretherapy predictors, which included demographic, diagnostic, and initial disturbance variables, significantly differentiated the two gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
72
0
8

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(91 citation statements)
references
References 27 publications
11
72
0
8
Order By: Relevance
“…These differences partly stem from gene translocations in RrF4 from the pTi to pAt plasmid, partly from unique sequences in both strains (Table 1). The acc operon, responsible for agrocinopine A+B uptake and catabolism, the arc operon for agrocinopine regulation of conjugation, a truncated version of the virH1 gene and the tra operon described by Piper et al (1999) were translocated in RrF4 from plasmid pTi to pAt. The latter one also includes the quorum sensing regulator gene traR but not the AHL synthase traI, which remains upstream of the trb operon on pTi in both strains.…”
Section: Resultsmentioning
confidence: 99%
“…These differences partly stem from gene translocations in RrF4 from the pTi to pAt plasmid, partly from unique sequences in both strains (Table 1). The acc operon, responsible for agrocinopine A+B uptake and catabolism, the arc operon for agrocinopine regulation of conjugation, a truncated version of the virH1 gene and the tra operon described by Piper et al (1999) were translocated in RrF4 from plasmid pTi to pAt. The latter one also includes the quorum sensing regulator gene traR but not the AHL synthase traI, which remains upstream of the trb operon on pTi in both strains.…”
Section: Resultsmentioning
confidence: 99%
“…Orlinsky et al (1994) examined successful and unsuccessful individual interventions, observing that the categories interpretation and support/empathy occurred with greater frequency in interventions that obtained positive results. Piper et al (1998) found a greater number (23%) of early interventions with a predominance of interpretation rather than support (6%). In the same direction, a recent study indicates that interpretation given in the first five sessions contribute to adherence of the client to the therapeutic process (Yano et al, 2008).…”
mentioning
confidence: 99%
“…However, there are still some diverging conclusions regarding dropout (Piper et al, 1998;Yano, Almeida & Meyer, 2008). Orlinsky et al (1994) examined successful and unsuccessful individual interventions, observing that the categories interpretation and support/empathy occurred with greater frequency in interventions that obtained positive results.…”
mentioning
confidence: 99%
“…Kazdin 9 propõe que três condições geralmente estão presentes na definição de abandono: 1) O paciente deixa o tratamento; 2) a decisão é tomada unilateralmente pelo paciente e 3) o terapeuta (ou equipe de trabalho) percebe a decisão como imprudente e prematura. A segunda condição é também enfatizada por muitos autores 4,8,22,28 , os quais preconizam em suas definições que o abandono se dá por decisão unilateral, ou seja, sem a concordância do terapeuta. Entretanto, há casos em que o terapeuta é comunicado pelo paciente de sua decisão de abandonar a terapia e, ainda assim, nada pode fazer para impedir o término dela -como nos casos em que o paciente perde sua fonte de renda ou muda-se de cidade, por exemplo.…”
Section: Resultsunclassified